Speaking of Jesus : essays on biblical language, gospel narrative, and the historical Jesus - Vorster, W. S. (Novum Testamentum, Supplements, 1999)
This volume presents a selection of essays by the late Willem Vorster, one of the most prominent New Testament scholars to have emerged from South Africa. An introductory essay by the editor explains Vorster's contribution to New Testament scholarship in general and to South African New Testament scholarship in particular. Vorster's essays are grouped primarily under the topics \'Language and Linguistics\', \'Reader Response\', \'Narratology\', \'Historical Paradigms\' and \'The Historical Jesus\'. In addition to his work on method, Vorster was a well-known Markan scholar, and this is reflected in the fact that more than half of his methodological essays are concerned with that Gospel. The book includes a curriculum vitae , a full bibliography and indexes.